Artificial Intelligence Dalam Autonomous Weapon Systems: Masalah Teknis atau Masalah Hukum? - Yuwono, Teguh; Harahap, Rahayu Repindowaty; Sipahutar, Bernard (Faculty of Law, Universitas Jambi, 2022)
This article discusses legal problems in the use of Artificial Intelligence (AI). In its development, AI has built human existence in various fields including the military. There is a problem when an Autonomous Weapon System (AWS) uses AI instead of a non-human operator. It was found that, AWS was unable to fulfill the principle of distinction and principle of proportionality set forth in article 51 paragraphs (1-3) and paragraph (5) of Additional Protocol I 1977. These principles are two solid matters, as they relate to the technical requirements expected on performance. field that can only be carried out by humans. Although AWS uses sensors as a distinguishing tool, it provides an estimate that this weapon system can apply the principle of discrimination. A discriminatory attack will also violate the law if it is not adjusted to the principle of proportionality. This is where the important role of humans in preventing unnecessary losses. In addition, the use of AI on AWS has also led to the disconnection of supervisory responsibilities that require superiors and subordinates. This is clearly what AWS does and a commander who gives the order to carry out the attack. For this reason, special arrangements are needed to regulate AWS in the form of a new convention or the addition of a protocol to The United Nations Convention on Certain Weapons 1980 with the aim of limiting the use of AI so that human presence remains in every use of weapons.